EVALUASI STRATEGI PEMASARAN PRODUK PEMBIAYAAN MULTIMANFAAT IB PADA MASA PANDEMI (STUDI KASUS BANK BTN SYARIAH KANTOR CABANG BEKASI) - Putra, Purnama; Putri, Elita Ichwan; Khoiriyah, Ummi (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
Bank BTN Syariah is a strategic business unit of PT Bank Tabungan Negara (BTN) Persero which focuses on improving business processes and the quality of the financing portfolio with sharia principles. However, there is a decline in the distribution of MultiManfaat (multi-merits) financing at BTN Syariah in the past year due to the Covid-19 pandemic. Therefore, to find out the adjustments in the marketing of financing products, an evaluation of the marketing strategy is needed. The formulation of alternative marketing strategies through analysis of Strengths, Weaknesses, Opportunities, Threats (SWOT) can be used as a formulation tool in formulating corporate strategies, starting by identifying internal and external environmental factors. Furthermore, the IFAS and EFAS matrices were compiled which became the basis for the preparation of the SWOT matrix and IE matrix so that the distribution of MultiManfaat IB financing products can immediately meet the target, and become a successful consumer financing product demanded by BTN Syariah customers. The results of the present study state that the condition of BTN Syariah KC Bekasi is in the Grow and Build positions.Â Keyword:Â Evaluation, IFAS & EFAS, Marketing Strategy